Empyema associated with Actinomyces georgiae successfully treated with multimodal therapy including surgical intervention: A first case report - Senichi Fukuda; Yuya Homma; Hiroki Kawakami; Soichiro Yamaji; Yuki Sato; Nao Sato; Reina Idemitsu; Taiki Kawai; Naoki Inoshima; Jun Hayashi; Norihiko Kubota; Tatsuya Nagai; et al. (Respiratory Medicine Case Reports, 2025)
A 77-year-old man presented with right-sided chest pain and dyspnea. Computed tomography revealed a loculated pleural effusion, and thoracentesis yielded purulent fluid. Actinomyces georgiae was identified using pleural fluid culture. Despite treatment with ampicillin-sulbactam and thoracic drainage, the patient's condition worsened, requiring video-assisted thoracoscopic surgery. The patient recovered completely after completing an 11-month course of antibiotics. This is the first reported case of empyema associated with A. georgiae. Actinomyces should be considered as a potential cause of empyema, and a comprehensive approach, including surgical intervention, is necessary for optimal management.